Measuring Inequalities in Shiraz Metropolis by Using Pandey and Nathwani Index - Mahmoud Akbari (جغرافیا و توسعه, 2014)
Income inequality Calculated by using Gini coefficient presents a narrow view of overall inequality in a society. The research focuses on its much broader definition, referred to as socio-economic inequality, which considers the disparities in income as well as in mortality, and standard of living. This article presents a new method for measuring the socio-economic inequality using a composite social indicator, Life Quality Index, derived from two principal indicators of development, namely, income and the life expectancy at birth. The study method Is Quantitative - analytical and territory of research Is nine regions of Shiraz city  in 2011. Using field data from the heads of households (384 households) have been collected, the state income stratum has been analyzed in Shiraz metropolitan region. Statistical Society of Shiraz is formed of households in the General Population and Housing Census 2006 was equal to 344 533 households. The sample size was calculated according to income stratum and a stratified random sampling of households in nine regions of Shiraz. The results show that the inequality index, showed  that the inequality criteria  in the study area is more than what is showed by   traditional criteria of Gini coefficient and other indicators of income inequality